Perceived Job Insecurity, Unemployment Risk and International Trade: A Micro-Level Analysis of Employees in German Service Industries - Maren Lurweg (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
The present paper investigates the impact of international trade on individual labour market outcomes in the German service sector for the period 1995-2006. Combiningmicro-level data from the German Socio-Economic Panel (SOEP) and industry-level trade data from input-output tables, we examine the impacts of international trade on (1) the individually reported fear of job loss and (2) job-to-unemployment transitions. We therefore apply both a "subjective" and a more "objective" measure of job insecurity. Our results indicate that international trade does indeed affect labour market outcomes in German service industries. Employees in trading service sectors face both a higher subjective and objective unemployment risk, regardless of their skill level. Moreover, growth in real net exports is positively correlated with perceived job insecurity and individual unemployment risk.
Keywords: F16; C23; J63; 330; International trade; perceived job insecurity; employment status; Beschäftigungssicherung; Arbeitslosigkeit; Wahrnehmung; Internationale Wirtschaft; Außenhandelssektor; Deutschland